Management of Low-Grade Third Ventricular Ependymomas in Adults by Endoscopic Biopsy Followed by Gamma Knife Radiosurgery - Kryzanski, James; Corliss, Brian; Rahal, Jason; Riesenburger, Ron; Hwang, Steven; Wu, Julian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background Third ventricular ependymomas in adults are rare lesions for which the optimal management strategy has not been determined.Objectives We describe our results using a strategy of endoscopic biopsy followed by gamma knife radiosurgery in two patients with low-grade (World Health Organization [WHO] grade II) third ventricular ependymomas.Methods A retrospective analysis of clinical notes, operative records, and neuroimaging was performed for the two patients in this study. The patients both presented with obstructive hydrocephalus and had endoscopic third ventriculostomy performed along with endoscopic tumor biopsy. In both patients the pathology revealed papillary ependymoma WHO grade II. In one patient the endoscopic third ventriculostomy failed, and ventriculoperitoneal shunt placement was necessary. Postoperatively, gamma knife radiosurgery was performed at 1 and 4 months, respectively.Results Both patients in the study experienced symptom resolution following treatment of the hydrocephalus. They returned to their preoperative level of social and occupational function. There was tumor enlargement in one patient in the interval between the initial surgery and the gamma knife treatment. However, neither tumor has enlarged since gamma knife treatment with follow-up of 35 and 41 months, respectively.Conclusions The strategy of endoscopic biopsy followed by gamma knife radiosurgery for adult WHO grade II third ventricular ependymomas has produced acceptable clinical results 3 years posttreatment. Stereotactic radiosurgery without prior microsurgical resection has not previously been reported in these tumors. Longer follow-up is required to evaluate the durability of this treatment.
Keywords: ependymoma; third ventricle; gamma knife